Communication Skills with Attention Deficit Hyperactivity Disorder Children Comparative Study between who are under the control of Behavioral Therapeutic and Behavioral & medicinal Therapeutic with Attention Deficit Hyperactivity Disorder children - Sobh, Safa; Sharrof, Ansab; Asaad, Amgad (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This study aimed at comparative in Communication Skills between who are under the control of Behavioral Therapeutic and Behavioral & medicinal Therapeutic with Attention Deficit Hyperactivity Disorder children. A random sample were selected consist of 34 children with ADHD, who visit the psycho-clinics : 14 for first group and 20 for second group aged 6-9 years old. Children with ADHD scaled by DSM-5, C. Kconners and Vineland Adaptive Behavior scales (Communication). The results didn’t reveal statistically significant differences in total score of Communication between both groups. Besides there weren’t statistically significant differences in branch dimensions of Communication (the Expressive language, the Receptive language, the Reading and writing) for children with ADHD between both groups.